Global Deep-Sea Biodiversity Research Trends Highlighted by Science Mapping Approach - Costa, Corrado; Fanelli, Emanuela; Marini, Simone; Danovaro, Roberto; Aguzzi, Jacopo (Frontiers in Marine Science, 2020)
The scientific literature available on deep-sea biodiversity is ample and covers a wide array of objectives, geographic areas and topics. It covers also the exploration of the links between ecosystem functioning and productivity, as well as modelling, management and exploitation. New informatics tools now allow the comprehensive monitoring of the status of deep-sea research, in order to highlight global research topics and their trends, which deserve further development and economic investments. Here, we used a science mapping approach to provide a global and systematic bibliometric synthesis of these current research topics and their trends, in order to identify the size, growth, trajectory, and geographic distribution of scientific efforts, as well as to highlight the emerging topics. A total of 1,287 deep-sea biodiversity publications were retrieved from the Scopus databases from 1993 to the present. Established and emerging research topics were identified: i. biogeochemical, microbial and molecular analyses; ii. biodiversity measures; iii. ecosystems conservation and management; and finally, iv. zoology and taxocoenosis. The temporal change in the research activity (by subdividing publications into 1993-2010 and 2011-2019 blocks) evidenced how the “biogeochemical, microbial and molecular analyses” cluster was not present from 1993 to 2010, since included in the one for “biodiversity measures”, showing emancipation in the following couple of decades. A dominant role in research of US followed by the United Kingdom, Germany and France was evidenced, with China particularly associated to the former.